Depression: analysis of epidemiological data on burden disease in Europe - Khaliq, R. N. (Запорізький державний медичний університет, 2016)
Today, depression is considered as one of the most common diseases. According to WHO, the beginning of the XXI century depressive disorders accounted about 40% in total mental pathology. Annually in the world about 200 million people suffer from depression, and this figure is actively growing. In this regard, the priority of health systems is an effective work aimed at the prevention and treatment of this disease. The aim of our study was to analyze the epidemiological data on the burden disease, depressive disorders caused by the results of the analytical data on network internet survey.